Migration pattern and impacts of labor migration among households in the Poblacion area of Miagao, Iloilo. - Castanares, Zyrian Lisa Conception; Lagura, Cecile Baradillo (2009.)
This study was designed to describe the migration pattern and the economic impacts of overseas labor migration among households in three selected barangays (Baybay Norte, Mat-y, and Tacas) in the poblacion area of Miagao, Iloilo. The data were gathered using two sets of interview schedules: one for the households with Overseas Filipino Workers (OFWs), and another for the households without OFWs. Descriptive statistics were used in analyzing the data. Results showed that households with OFWs had a higher standard of living than thoses without OFWs based on material lifestyle indicators. Household with OFWs earned higher annual household income (sum of annual domestic earnings, annual remittance and annual external help) than those households withour OFWs. About 61% of the income of households with OFWs is from remittance. Expenditures on basic necessities, education, savings and housing improvements among households with OFWs were largely financed by remittance. A higher number of assets and housing conveniences were owned by households with OFWs. Remittances were mostly used in purchasing these. Dwellings of a large percentage of households with OFWs were well-furnished and were made-up of concrete and galvanized roof. Most of the OFWs in this study were sea-based. Most were hired by shipping companies found in the Asian region specifically by Philippine-owned companies. A large percentage of land-based OFWs were working in Middle East. They were mostly involved in service works such as domestic help, factory work, and care giving.
Thesis (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2009.
Keywords: Labor migration -- Miagao, Iloilo